2018
DOI: 10.1667/rr14840.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiation Promotes Dendritic Cell Migration and IL-12 Production via the ATM/NF-KappaB Pathway

Abstract: For dendritic cells (DCs) to initiate an immune response, their ability to migrate and to produce interleukin-12 (IL-12) is crucial. It has been previously shown that low-dose radiation (LDR) promoted IL-12 production by DCs, resulting in increased DC activity that contributed to LDR hormesis in the immune system. However, the molecular mechanism of LDR-induced IL-12 production, as well as the effect of LDR on DC migration capacity require further elucidation. Using the JAWSII immortalized mouse dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In regard of the underlying mechanisms of LDIR’s effects on skin structures, it was reported that LDIR promoted IL-12 production, dendritic cells migration [ 10 ], and skin-infiltrating monocytes/macrophages migration to draining lymph nodes [ 11 ]. Interestingly, ionizing radiation affects not only the directly irradiated cells but also non-irradiated neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…In regard of the underlying mechanisms of LDIR’s effects on skin structures, it was reported that LDIR promoted IL-12 production, dendritic cells migration [ 10 ], and skin-infiltrating monocytes/macrophages migration to draining lymph nodes [ 11 ]. Interestingly, ionizing radiation affects not only the directly irradiated cells but also non-irradiated neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…This immunosuppression is especially problematic when STAT3 is activated, because it is the key transcriptional factor that renders tumor-infiltrating dendritic cells dysfunctional (53). Because WBRT triggers the activation and influx of the dendritic cells (54)(55)(56), and because STAT3 blockade reverses the immunosuppressive glioma microenvironment (8,11,28) this scenario. Alternatively, the observed dendritic cell and T-cell interactions may represent and support the notion of the secondtouch hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found the upregulation of genes involved in NF-κB activation and oxidative stress in the gut of abandoned pigs, through microarray analysis (Table 11.1). Yu et al demonstrated that LDR radiation promotes dendritic cell migration and IL-12 secretion through the NF-κB pathway [25]. IL-12 is one of the most important cytokines for the initiation of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%